Electrochemical performance of flexible polyethylene terephthalate-based dye-sensitized solar cell - Tan, Jian Hua (2017)
Our earth’s natural resources are being depleted at an alarming rate. Green energy is now in greater demand than ever as our resources are being consumed faster than they can be replenished. Hence, solar energy, the best form and source of renewable energy, can fulfil the ever-increasing demand for more and more energy. Therefore, the invention of the 3rd generation solar cell, otherwise known as the dye-sensitized solar cell (DSSC), can meet this demand and help overcome the dependence on fossil fuels and the like. The DSSC is very effective and efficient as it can perform in low-light conditions. It is very cost efficient as well when compared to previous generations of solar cells. In the present study, indium tin oxide coated on polyethylene terephthalate (ITO/PET) was utilized as the flexible substrate for both the photoanode and the counter electrode in the dye-sensitized solar cell (DSSC). The main objective of this study was to find out the performance of DSSCs sintered at different temperatures during the fabrication process. The photoanode comprising of a layer of titanium dioxide on an ITO/PET substrate (TiO2/ITO/PET) was prepared by mild sintering at 140, 150, 160, 170 and 180 °C. Secondly, the intention of this study was to find out the effect different photoanode active area sizes have on the performance of the DSSC which had the best performance among samples from the previous step. The active areas of the photoanodes were set at 1.0 cm2, 0.25 cm2, and 0.09 cm2. The DSSC assembly is incomplete without a counter electrode. The counter electrode is made bybinding the polypyrrole and graphene oxide onto an ITO/PET substrate (PPy/rGO/ITO/PET). It was prepared using electrodeposition and was used in place of platinum for the counter electrode. Lastly, the study set out to test whether the DSSC works when in a bent condition. A cyclic voltammetry analysis showed that electron charge transfer occurs on the sensitized photoanode sintered at temperatures ranging from 140 - 180 °C during the fabrication process. The photoanode samples exhibited two anodic potential peaks, the first ranging from 0.70 V to 0.74 V and the second from 1.0 V to 1.3 V. However, no cathodic potential peak was seen, thus indicating that the oxidized ruthenium dye (N719) molecules have a short lifespan. The photoanode sample sintered at 160 °C gave the best efficiency when compared to samples sintered at other temperatures. The same photoanode with an active area of 0.25 cm2 displayed the best performance with an open circuit voltage (Voc) of 0.63 V, a short circuit current density (Jsc) of 3.0 mA cm-2, and an efficiency (η) of 0.91% under 1 sun illumination (100mW cm-2, AM 1.5G). Last but not least, the ITO/PET-based DSSC continues to work when bent albeit at a reduced efficiency.